Plastome Evolution in Saxifragaceae and Multiple Plastid Capture Events Involving Heuchera and Tiarella - Liu, Lu-Xian; Du, Ying-Xue; Folk, Ryan A.; Wang, Shen-Yi; Soltis, Douglas E.; Shang, Fu-De; Li, Pan (Frontiers in Plant Science, 2020)
Saxifragaceae, a family of over 600 species and approximately 30 genera of herbaceous perennials, is well-known for intergeneric hybridization. Of the main lineages in this family, the Heuchera group represents a valuable model for the analysis of plastid capture and its impact on phylogeny reconstruction. In this study, we investigated plastome evolution across the family, reconstructed the phylogeny of the Heuchera group and examined putative plastid capture between Heuchera and Tiarella. Seven species (11 individuals) representing Tiarella, as well as Mitella and Heuchera, were selected for genome skimming. We assembled the plastomes, and then compared these to six others published for Saxifragaceae; the plastomes were found to be highly similar in overall size, structure, gene order and content. Moreover, ycf15 was lost due to pseudogenization and rpl2 lost its only intron for all the analyzed plastomes. Comparative plastome analysis revealed that size variations of the plastomes are purely ascribed to the length differences of LSC, SSC, and IRs regions. Using nuclear ITS+ETS and the complete plastome, we fully resolved the species relationships of Tiarella, finding that the genus is monophyletic and the Asian species is most closely related to the western North American species. However, the position of Heuchera species was highly incongruent between nuclear and plastid data. Comparisons of nuclear and plastid phylogenies revealed that multiple plastid capture events have occurred between Heuchera and Tiarella, through putative ancient hybridization. Moreover, we developed numerous molecular markers for Tiarella (e.g., plastid hotspot and polymorphic nuclear SSRs), which will be useful for future studies on the population genetics and phylogeography of this disjunct genus.